ANALISIS KARAKTER ŚAKUNI DALAM KISAH MAHĀBHĀRATA PADA SITUASI MENJELANG KONTESTASI POLITIK 2024 - Darma Permana, I Dewa Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The presence of General Elections as an arena for political contestation brings several challenges to its dynamics. The challenges of the General Election lead to the presence of identity politics, money politics, black campaigns, and other challenges. Some of these challenges have actually been reflected through one of the characters in the Mahābhārata story, namely Śakuni. Based on this, the researcher in this case is interested in analyzing the character of Śakuni and then linking it to the situation before the political contestation in Indonesia. Based on this topic, three problem formulations are presented, including: The essence of the Mahābhārata story, Śakuni's actions, and the analysis of Śakuni's character in responding to the situation before the General Election. This research uses descriptive qualitative research with a philosophical hermeneutic approach. Data sources come from literature studies and data processing using the Miles and Huberman analysis pattern. The result of this research is that the character analysis of Śakuni in the situation before the General Election has a contextual connection. This concerns the existence of money politics, black campaigns, and identity politics that can threaten the dynamics of politics in Indonesia. This paper aims to serve as a guideline in the formation of smart and wise voters.